Performance Test of Biomass Cookstove with Torrefied Rice Husk as Fuel Using Water Boiling Test Method - Alwan, Hafid; Irawan, Anton; Santika, Santika; Nurindah, Erlin (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2020)
One of the way to increase effectiveness and efficiency of using biomass as fuel is through gasification cookstove technology. Gasification cookstoves is tools used to convert biomass into combustible gases via thermochemical pathline. Rice husk is a type of biomass that has a low heating value of 14 MJ/Kg. Therefore, it is necessary to pre-treat it through torefaction to increase the calorific value of the fuel so that it can increase the thermal efficiency of the gasification cookstove. This research was conducted to obtain the optimum conditions for air flow rate, height of the bed, and fuel type of rice husk torrefied. This research was conducted by inserting rice husk torrefied as fuel with a variation of height of the bed 42.6 cm; 31.5 cm; and 21.3 cm, the secondary air flow rate openings (full open; partial open; close), and type of fuel used is the rice husk torrefied at temperature 250 oC for 60 minutes (fuel A), and temperature 300 °C for 30 minutes (fuel B). The optimum operating conditions were found at 21.3 cm of bed height, full close secondary air opening, with type A fuel. While the highest efficiency value of 18.75% was found in type A fuel, with bed height 31.5 cm, and secondary air opening is full close.